EFEKTIVITAS PENGGUNAAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR IPS SMPN 21 PONTIANAK - Herman, Herman; Aminuyati, Aminuyati; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out about "the effectiveness of using cooperative script learning models on student learning outcomes in social studies subjects in class VIII A in Pontianak Public Middle School". The research method used is descriptive method with the form of research used is Experiments (one group pre-test post-tets). The variables in this study are independent and bound variables which are independent variables, namely "the use of cooperative script learning models, while the dependent variable is" learning outcomes of class VIII A. "The data source in this study is the learning outcomes of class VIII A students. multiple choice tests and observations, interviews, and documentary study sheets To analyze the data using descriptive analysis The results of hypothesis testing used the Kolmogorov smirnov normality test with a significance value of 0.460> 0.05 with a normally distributed residual, then an independent sample test t-test with a value sig. -tailed) = 0.00 <0, 05, in the field of rejection Ho and Ha accepted, calculation of effect size = 2.0430 contributes to the high category the value of IPS lessonsKeywords: Effectiveness, Cooperative Script Learning Model, Learning Outcomes Â Â